Faith alone the evangelical doctrine of justification - Sproul, Robert Charles, 1939- (Grand Rapids, MI Baker, 1995)
Includes bibliographical references and index.
Keywords: Justification (Christian theology) -- history of doctrines; Reformed church -- doctrines